COMPARING CREATININE TO UREA VOLUME (KT/V) AMONG ARTERIOVENOUS FISTULA, VASCULAR GRAFT, AND TUNNELED CUFFED CATHETERS: A RETROSPECTIVE STUDY - HAIDER, A; RAZZAQUE, MRA; KHAN, AR (Biological and Clinical Sciences Research Journal, 2024)
Hemodialysis patients may employ three different kinds of vascular access: permanent catheter (PC), arteriovenous fistula (AVF), and vascular graft (AVG). This research was done to compare AVF, AVG, and PC regarding dialysis adequacy since there is a lack of data on the subject. Methods: This was a two-year retrospective study. Two hundred hemodialysis patients participated in the research and were randomly allocated to one of three groups: AVF, AVG, or PC. Blood was drawn before and after a dialysis treatment to analyze the urea reduction ratio (URR) and creatinine to urea volume (Kt/V). Laboratory tests were redone after six months of monitoring the patients. Results: A total of 200 patients were divided into three groups based on the type of vascular access: AVF (n=137), AVG (n=36), and PC (n=27). The Mean ± S.D of the patient’s age in AVF, AVG, and PC were 58.6±14.7, 60.5±0.5, and 53.6±25.0 years respectively. The Mean ± S.D of Kt/v in AVF, AVG, and PC were 1.2±0.3, 1.4±0.2, and 1.1±0.4 respectively. A significant Variation (p=0.012) in the mean Kt/v of the study groups was observed in the present study. The Mean ± S.D of URR in AVF, AVG and PC were 64.3±7.9, 69.1±3.1, and 62.8±5.1 respectively. A significant Variation (p=0.000) in the mean URR of the study groups was observed in the present study. Conclusion: AVF and AVG have superior hemodialysis adequacy regarding Kt/v and URR over PC.